Simulation of Cl- secretion in epithelial tissues: New methodology estimating activity of electro-neutral Cl- transporter - Kouhei eSasamoto (Frontiers in Physiology, 2015)
Transcellular Cl- secretion is, in general, mediated by two steps; 1) the entry step of Cl- into the cytosolic space from the basolateral space across the basolateral membrane by Cl- transporters, such as Na+-K+-2Cl- cotransporter (NKCC1, an isoform of NKCC), and 2) the releasing step of Cl- from the cytosolic space into the luminal (air) space across the apical membrane via Cl- channels, such as cystic fibrosis transmembrane conductance regulator (CFTR) Cl- channel. Transcellular Cl- secretion has been characterized by using various experimental techniques. For example, measurements of short-circuit currents in the Ussing chamber and patch clamp techniques provide us information on transepithelial ion movements via transcellular pathway, transepithelial conductance, activity (open probability) of single channel, and whole cell currents. Although many investigators have tried to clarify roles of Cl- channels and transporters located at the apical and basolateral membranes in transcellular Cl- secretion, it is still unclear how Cl- channels/transporters contribute to transcellular Cl- secretion and are regulated by various stimuli such as Ca2+ and cAMP. In the present study, we simulate transcellular Cl- secretion using mathematical models combined with electrophysiological measurements, providing information on contribution of Cl- channels/transporters to transcellular Cl- secretion, activity of electro-neutral ion transporters and how Cl- channels/transporters are regulated.